STUDENTS' CRITICAL THINKING ABILITIES IN SOLVING FINAL YEAR SUMMATIVE ASSESSMENT (ASAT) QUESTIONS FOR SCIENCE SUBJECTS IN GRADE IV PRIVATE ELEMENTARY SCHOOLS IN KUTOARJO - Elsa Agustina; S Eko Putro Widoyoko; Nur Ngazizah (Universitas Majalengka, 2026)
Critical thinking skills are one of the important skills that need to be developed in 21st century learning. In the Natural and Social Sciences (IPAS) subject, critical thinking skills are needed to solve problems that require Higher Order Thinking Skills (HOTS). However, assessments in elementary schools are still dominated by questions oriented to Lower Order Thinking Skills (LOTS), so students' critical thinking skills have not been optimally measured. This study aims to analyze students' critical thinking skills in solving the Year-End Summative Assessment (ASAT) questions for science subjects grade IV Private Elementary School in Kutoarjo. This study used a qualitative descriptive approach involving 24 students in grade IV, while five students were selected purposively as the main subjects of the study. Data was collected through documentation, observation, and interviews, then analyzed using the Miles and Huberman models. The results showed that of the 30 ASAT questions analyzed, as many as 18 questions (60%) were included in the LOTS category and 12 questions (40%) were included in the HOTS category. Students' critical thinking skills are divided into the categories of Developing Very Good (20%), Developing as Expected (40%), and Starting to Develop (40%) based on the achievement of Ennis' critical thinking indicators, namely focus, reason, inference, situation, clarity, and overview. Students in the Very Well Developed category were able to meet most of the critical thinking indicators and showed better ability to solve HOTS questions, while students in the Developing Beginning category still had difficulty in giving reasons, drawing conclusions, and evaluating answers. The findings of the study show that the better the students' critical thinking skills, the better their ability to solve HOTS problems in science subjects.